Sustainable, Renewable and Environmental-Friendly Insulation Systems for High Voltages Applications - Muhammad Rafiq; Muhammad Shafique; Anam Azam; Muhammad Ateeq; Israr Ahmad Khan; Abid Hussain (Molecules, 2020)
With the inception of high voltage (HV), requisites on the insulating permanence of HV equipment is becoming increasingly crucial. Mineral/synthetic oil liquid insulation—together with solid insulation materials (paper, pressboard)—is the fundamental insulation constituent in HV apparatuses; their insulation attributes perform a substantial part in a reliable and steady performance. Meanwhile, implications on the environment, scarcity of petroleum oil supplies and discarding complications with waste oil have stimulated investigators to steer their attention towards sustainable, renewable, biodegradable and environmentally friendly insulating substances. The contemporary insulating constituent’s evolution is driven by numerous dynamics—in particular, environmental obligations and other security and economic issues. Consequently, HV equipment manufacturers must address novel specifications concerning to these new standards. Renewable, sustainable and environmentally friendly insulating materials are continuously substituting conventional insulating items in the market place. These are favorable to traditional insulating materials, due to their superior functionality. The also offer explicit security and eco-friendly advantages. This article discusses cutting-edge technology of environmentally friendly insulating materials, including their fabrication, processing and characterization. The new renewable, insulating systems used in HV equipment are submitted and their fundamental gains stated in comparison with conventional insulating materials. Several experimental efforts carried out in various parts of the world are presented, offering an outline of the existing research conducted on renewable insulating systems. The significance of this article lies in summarizing prior investigations, classifying research essence, inducements and predicting forthcoming research trends. Furthermore, opportunities and constraints being experienced in the field of exploration are evidently reported. Last but not least, imminent research proposals and applications are recommended.